PULMONARY FUNCTION IN RHEUMATOID ARTHRITS: A CROSS-SECTIONAL STUDY - MALODE, AISHWARYA; YADAV, R N; GOYAL, GIRDHAR GOPAL; JAIN, GUNJA; MATHUR, AJAY; GOYAL, LAXMIKANT (International Journal of Current Pharmaceutical Research, 2024)
Objective: Rheumatoid arthritis (RA) is an autoimmune disease with many extraarticular manifestations. Pulmonary involvement is seen in 60-80% cases with and without symptoms. This research studies the pattern of PFT (Pulmonary Function Test) in RA and find the correlation between PFT and Disease activity. Secondary objectives were to evaluate the effect of use of Methotrexate (MTx) on disease activity and PFT. Methods: An outpatient-based descriptive cross-sectional study was conducted in General Medicine department at a tertiary centre among 100 eligible patients. Disease activity score was recorded using DAS-28 (Disease Activity Score-28) and CDAI (Clinical Disease Activity Index). Patients underwent PFT by Spirometry thereafter. Results: 45 % patients had restrictive pattern and 55% had normal PFT. None had an obstructive pattern. The mean FVC (Forced Vital Capacity), FEV1 (Forced Expiratory Volume in the first second), FEV1/FVC ratio, PEFR (Peak Expiratory Flow Rate) and FEF 25-75% (Forced mid expiratory flow) were 78.83±14.37, 79.24±16.96, 103.56±11.03, 71.73±22.39 and 76.56±23.72 respectively. Both FVC and FEV1 were found to be significantly associated with age, disease duration, CDAI score, MTx dose and duration (P<0.05). Age, ESR(erythrocyte sedimentation rate) and MTx dose were significantly associated with FEV1/FVC ratio (P<0.05). Age, duration of disease, ESR. MTx dose and duration were significantly associated with PEFR (P<0.05). Lastly age, CDAI score, MTx dose and duration were significantly associated with FEF 25-75% (P<0.05). Conclusion: Restrictive pattern (45%) was the most common defect on PFT among RA patients. Severity of lung disease depends on age, MTx dose, disease activity (ESR, CDAI), duration of disease and MTx duration.